Suitable Media for Culturing the Diatom, Thalassiosira sp. in the Laboratory - ศรีพนมยม จักรพงษ์; กาญจนสมบูรณ์ ศศิกานต์ (KKU Science Journal, 2012)
Culturing of the diatom, Thalassiosira sp. was conducted in the laboratory with an average of 105 cells/ml at 28 ± 1 ºC, pH 7.5 ± 0.2 and light intense of 4,000 lux. Four types of media were AGP (commercial grade), Guillard (F/2), Conway and Conway modified (MF) were compared. The growth was recorded every 6 hours until to the maximum cell density was reached. The continuing culture was finished when the cell density decreased 4 times within 24 hr. The results showed the maximum cell density of AGP, F/2, Conway and MF medium were 6.47 ± 0.198, 6.18 ± 0.168, 5.89 ± 0.198 and 9.08 ± 0.307 × 105 cells/ml, respectively. MF medium showed the highest time interval followed by Conway, F/2 and AGP with 156, 144, 102 and 96 hr., respectively. The statistical analysis showed significant differences in maximum density between MF medium and the other media. The cell size decreased in series form AGP, F/2, Conway and MF medium. The average cell widths were 7.74 ± 1.07, 7.16 ± 1.21, 6.47 ± 1.01 and 5.92 ± 0.93 micrometers, respectively. The average cell lengths were 18.17 ± 0.51, 16.41 ± 1.03, 15.26 ± 1.12 and 15.07 ± 1.04 micrometers, respectively. Abnormal cells and contamination were not recorded. pH ranged from 7.76-8.37, nitrate, nitrite, ammonia, orthophosphate and total phosphorus varied form 0.94-2.20, 0.005-0.086, 0.010-1.577, 0.013-0.165 and 0.078-0.528 mg/l, respectively.